Tunnelling spectroscopy of Andreev states in graphene - Bretheau, Landry; Wang, Joel I-Jan; Pisoni, Riccardo; Watanabe, Kenji; Taniguchi, Takashi; Jarillo-Herrero, Pablo (Nature physics, 2017)
Van der Waals heterostructures provide a tunable platform for probing the Andreev bound states responsible for proximity-induced superconductivity, helping to establish a connection between Andreev physics at finite energy and the Josephson effect. A normal conductor placed in good contact with a superconductor can inherit its remarkable electronic properties 1 , 2 . This proximity effect microscopically originates from the formation in the conductor of entangled electron–hole states, called Andreev states 3 , 4 , 5 , 6 , 7 , 8 . Spectroscopic studies of Andreev states have been performed in just a handful of systems 9 , 10 , 11 , 12 , 13 . The unique geometry, electronic structure and high mobility of graphene 14 , 15 make it a novel platform for studying Andreev physics in two dimensions. Here we use a full van der Waals heterostructure to perform tunnelling spectroscopy measurements of the proximity effect in superconductor–graphene–superconductor junctions. The measured energy spectra, which depend on the phase difference between the superconductors, reveal the presence of a continuum of Andreev bound states. Moreover, our device heterostructure geometry and materials enable us to measure the Andreev spectrum as a function of the graphene Fermi energy, showing a transition between different mesoscopic regimes. Furthermore, by experimentally introducing a novel concept, the supercurrent spectral density, we determine the supercurrent–phase relation in a tunnelling experiment, thus establishing the connection between Andreev physics at finite energy and the Josephson effect. This work opens up new avenues for probing exotic topological phases of matter in hybrid superconducting Dirac materials 16 , 17 , 18 .